Transition Metal Complexes with Sulfur Ligands. 130.(1) Synthesis, Structure, and Reactivity of the Sulfur-Rich Ruthenium Hydride Complexes [Ru(H)(PR(3))('S(4)')](-) and the eta(2)-H(2) Complex [Ru(H(2))(PCy(3))('S(4)')] (R = Ph, (i)Pr, Cy; 'S(4)'(2-) = 1,2-Bis((2-mercaptophenyl)thio)ethane(2-)). - Sellmann, Dieter; Gottschalk-Gaudig, Torsten; Heinemann, Frank Wilhelm (Inorganic Chemistry, 1998)
Hydride and eta(2)-H(2) ruthenium complexes with sulfur-rich coordination spheres were synthesized. Substitution of either DMSO or PPh(3) in [Ru(DMSO)(PR(3))('S(4)')] and [Ru(PPh(3))(2)('S(4)')] by hydride anions from LiAlH(4) or NaBEt(3)H yielded [Ru(H)(PR(3))('S(4)')](-) complexes (R = (i)Pr, Ph, Cy; 'S(4)'(2)(-) = 1,2-bis((2-mercaptophenyl)thio)ethane(2-)). They were isolated as [Li(THF)(Et(2)O)][Ru(H)(PR(3))('S(4)')] (R = (i)Pr (1a), Cy (1b), Na[Ru(H)(PCy(3))('S(4)')].2BEt(3).0.5DMSO (2a), and the solvent-free Na[Ru(H)(PPh(3))('S(4)')].2BEt(3) (2b). X-ray structure determinations of 1a.0.5Et(2)O and 1b.Et(2)O showed that in both complexes pseudooctahedral [Ru(H)(PR(3))('S(4)')](-) anions are bridged to pseudotetrahedral [Li(THF)(Et(2)O)] cations via the hydride ligand and one thiolate donor of the 'S(4)'(2)(-) ligand (crystal data: 1a, monoclinic, P2(1)/n, a = 1401.6(2) pm, b = 1045.2(3) pm, c = 2590.6(4) pm, beta = 95.04(1) degrees, V = 3.780(1) nm(3), Z = 4; 1b, triclinic, P&onemacr;, a = 1264.2(1) pm, b = 1322.9(3) pm, c = 1569.5(2) pm, alpha = 88.96(1) degrees, beta = 83.48(1) degrees, gamma = 62.16(1) degrees, V = 2.3042(6) nm(3), Z = 2). Short intramolecular C-H.H-Ru contacts ( approximately 230 pm) between the hydride ligands, phosphine substituents, and lithium-coordinated Et(2)O molecules indicate "unconventional" hydrogen bonds. They potentially help to decrease the hydridic character of the hydride ligand to such an extent that no structural hydride trans influence can be observed in the solid state. In solution at room temperature, all hydride complexes 1a-2b rapidly release H(2) or HD, when treated with CH(3)OH or CD(3)OD. Low-temperature (1)H and (2)H NMR spectroscopy between -20 and -80 degrees C showed that initially eta(2)-H(2) or eta(2)-HD complexes form. Their formation explains the observed scrambling between protons and hydride ligands, which requires a heterolytic cleavage of dihydrogen. A 1:1:1 triplet at delta = -6.5 ppm ((1)J(HD) = 32 Hz, (2)J(PH) = 5 Hz) and a relaxation time of T(1)(min) = 4 ms (-60 degrees C, 270 MHz) firmly established the formation of the eta(2)-dihydrogen complexes. The reversibility of H(2) release and uptake by [Ru(PCy(3))('S(4)')] fragments and the heterolytic cleavage of H(2) in [Ru(eta(2)-H(2))(PCy(3))('S(4)')] was further ascertained by the reaction of [Ru(DMSO)(PCy(3))('S(4)')] with H(2) in the presence of NaOMe, yielding the [Ru(H)(PCy(3))('S(4)')](-) anion. The relevance of the complexes and their reactions for the heterolytic H(2) activation at the transition metal sulfur sites of hydrogenases is discussed.